2021
DOI: 10.1002/pbc.29351
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination rates and hospitalizations among Medicaid enrollees with and without sickle cell disease, 2009–2015

Abstract: Background: Personswith sickle cell disease (SCD) face increased risks for pulmonary and infection-related complications. This study examines influenza vaccination coverage and estimates influenza-related morbidity among Medicaid enrollees with and without SCD. Procedure: Influenza vaccination coverage and hospitalizations related to influenza and pneumonia/acute chest syndrome (ACS) during each influenza season from 2009-2010 to 2014-2015 were assessed among enrollees in the IBM MarketScan® Multi-State Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is promising that most participants in our sample reported that they or their child received the 2020/2021 influenza vaccine; our rates were higher than previous reports 29,30 . Studies have shown those who receive one recommended vaccine are more likely to receive other recommended vaccines.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…It is promising that most participants in our sample reported that they or their child received the 2020/2021 influenza vaccine; our rates were higher than previous reports 29,30 . Studies have shown those who receive one recommended vaccine are more likely to receive other recommended vaccines.…”
Section: Discussionmentioning
confidence: 46%
“…It is promising that most participants in our sample reported that they or their child received the 2020/2021 influenza vaccine; our rates were higher than previous reports. 29 , 30 Studies have shown those who receive one recommended vaccine are more likely to receive other recommended vaccines. 31 , 32 However, given that there has been an overall decline in influenza vaccine rates, 33 interventions to address the combination of the influenza and COVID-19 vaccines may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased risk of serious morbidity associated with COVID‐19 among individuals with SCD, and the ability of the vaccine to decrease some of this risk, COVID‐19 vaccine uptake was suboptimal among adolescent patients and household caregivers of children with SCD. This low uptake of the COVID‐19 vaccine appears to be consistent with suboptimal uptake of the seasonal influenza vaccine among patients with SCD 2,7 . At the time of survey collection, younger children were not vaccine‐eligible outside of a clinical trial, hence younger children were not included in this study.…”
Section: Discussionmentioning
confidence: 86%
“…2,7 At the time of survey collection, younger children were not vaccine-eligible outside of a clinical trial, hence younger children were not included in this study. Nevertheless, we have not observed changes in vaccine attitudes among clinic patients since the approval of COVID-19 vaccines for younger children.…”
mentioning
confidence: 99%
“…The objective of this work is to estimate influenza vaccination rates among Medicaid enrollees using Medicaid claims data. Previous studies have been conducted to evaluate influenza vaccine uptake among individuals with pre-existing medical conditions including rheumatic or malignant diseases, sickle cell disease, and chronic kidney or liver disease, but few studies have been conducted among pregnant persons or individuals with diabetes or other comorbidities who make up a large proportion of the Medicaid population [20][21][22]. We hypothesize that people with at-risk conditions (i.e., diabetes, pregnancy) are more likely to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%